Respostas
respondido por:
3
4x + 2y = - 2 ÷2
2x + 3y = - 7
2x+y=-2
2x+3y=-7
y=-2-2x
y=-2-2*(1/4)
y=-2-1/2
MMC de 2 e 1 = 2
y=-4/2-1/2
y=-5/2
2x+3*(-2-2x) = -7
2x+ (-6) -6x = -7
2x-6-6x=-7
2x-6x=-7+6
-4x=-1
x=-1/-4
x=1/4
2x + 3y = - 7
2x+y=-2
2x+3y=-7
y=-2-2x
y=-2-2*(1/4)
y=-2-1/2
MMC de 2 e 1 = 2
y=-4/2-1/2
y=-5/2
2x+3*(-2-2x) = -7
2x+ (-6) -6x = -7
2x-6-6x=-7
2x-6x=-7+6
-4x=-1
x=-1/-4
x=1/4
LLucas1:
Obgd
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás